PENGUATAN KUALITAS INFRASTRUKTUR PENDIDIKAN MELALUI PENDAMPINGAN PROGRAM REVITALISASI SMA DI PROVINSI ACEH - Michel Kasaf; Alfisyahrin; Mhd. Arief Diana; Tjut Rizqi Maysyarah Hadi; Marini Bravikawati (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2025)
The Senior High School (SMA) Revitalization Program is a strategic government initiative aimed at improving the quality of educational infrastructure to support a safe, comfortable, and sustainable learning environment. However, its implementation still encounters various technical and managerial challenges, particularly during the planning, execution, and control stages of the work. This community service activity aims to strengthen the quality of educational infrastructure through assistance in the SMA Revitalization Program in Aceh Province. The assistance was carried out by a university team using a self-managed approach, providing technical assistance, field supervision, and administrative support to schools and relevant stakeholders. The implementation methods included identification of existing conditions, assistance in technical planning, monitoring of construction implementation, and evaluation of work outcomes. The results indicate that the assistance improved the technical understanding of school-level implementers, enhanced the quality of construction work, and minimized potential implementation errors. Therefore, this activity contributes positively to the successful implementation of the SMA Revitalization Program and to the improvement of educational infrastructure quality in Aceh Province.